Rare presentation of bardet-biedl syndrome as chronic liver disease with splenomegaly - J Manjula; K Ravi; V N Prashanth (Wolters Kluwer Medknow Publications, 2020)
Bardet-Biedl syndrome is a rare ciliopathic human autosomal-recessive disorder. It is a disorder that affects many parts of the body. Less than 15 cases have been reported from India. The signs and symptoms of this condition vary among affected individuals, even among members of the same family. It is characterized principally by the cardinal symptoms of marked central obesity, retinal dystrophy, polydactyly, mental retardation, hypogonadism, and renal dysfunction. The frequency of the syndrome is estimated to be 1:160,000.